Global cross-cultural validation of a brief measure for identifying potential suicide risk in 42 countries - Gewirtz-Meydan, A; Koós, M; Nagy, L; Kraus, S W; Demetrovics, Z; Potenza, M N; Ballester-Arnal, R; Batthyány, D; Bergeron, S; Billieux, J; Burkauskas, J; Cárdenas-López, G; et al. (Public health, 2024)
OBJECTIVES: This study aimed to examine the psychometric properties of the P4 suicide screener in a multinational sample. The primary goal was to evaluate the reliability and validity of the scale and investigate its convergent validity by analyzing its correlation with depression, anxiety, and substance use. STUDY DESIGN: The study design is a cross-sectional self-report study conducted across 42 countries. METHODS: A cross-sectional, self-report study was conducted in 42 countries, with a total of 82,243 participants included in the final data set. RESULTS: The study provides an overview of suicide ideation rates across 42 countries and confirms the structural validity of the P4 screener. The findings indicated that sexual and gender minority individuals exhibited higher rates of suicidal ideation. The P4 screener showed adequate reliability, convergence, and discriminant validity, and a cutoff score of 1 is recommended to identify individuals at risk of suicidal behavior. CONCLUSIONS: The study supports the reliability and validity of the P4 suicide screener across 42 diverse countries, highlighting the importance of using a cross-cultural suicide risk assessment to standardize the identification of high-risk individuals and tailoring culturally sensitive suicide prevention strategies.
Keywords: Reproducibility of Results; Cross-cultural; Suicide; Assessment; Suicidal Ideation; Suicide Prevention; lidé; reprodukovatelnost výsledků; Psychometrics; sebevražedné myšlenky; Cross-Sectional Studies; Validation; psychometrie; srovnání kultur; Cross-Cultural Comparison; prevence sebevražd; průřezové studie; Humans